PERAN ORANG TUA DALAM MEMBANGUN KEPRIBADIAN ANAK - Arsam, Arsam (Fakultas Dakwah IAIN Purwokerto, 2012)
One of parents’ roles in family life is delivering religious values. This can beapplied in the family in three methods, bilhikmah (wisely), bilmauidzhoh hasanah (withgood advice), and bilmujadalah (with exchange thoughts). These methods are applied inorder to form good character of children. In applying this method effectively andefficiently, parents as a performer da’i should apply ten guidance for da’i.The ten rules are: 1) parents should provide exemplary before preaching; 2) parentsshould have good impression; 3) parents should explain before giving someassignment/task; 4) parents have to apply some phases in giving tasks; 5) parents shouldfacilitate rather than complicate; 6) the principles should be given before the branch; 7)parents should motivate rather than threat; 8) parents should encourage rather than dictate;9)parents should educate rather than expose; 10) parents should emphasize students tofrom their teacher rather than from books.